2018
DOI: 10.9778/cmajo.20170163
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of successful and earlier pleurodesis with a tunnelled pleural catheter in malignant pleural effusion: a cohort study

Abstract: Clinicians should consider numerous factors to predict the probability of and timing to pleurodesis with tunnelled pleural catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…To our knowledge, this is the first published description of use of a shortened PleurX catheter for the ambulatory management of MPEs. We found that complication rates were low, and like previously published complication rates for the standard length PleurX catheter from our center 8. We also found that a large majority of nursing staff familiar with both catheters preferred the shorter catheter because of ease of use.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…To our knowledge, this is the first published description of use of a shortened PleurX catheter for the ambulatory management of MPEs. We found that complication rates were low, and like previously published complication rates for the standard length PleurX catheter from our center 8. We also found that a large majority of nursing staff familiar with both catheters preferred the shorter catheter because of ease of use.…”
Section: Discussionsupporting
confidence: 84%
“…Indwelling pleural catheters (IPCs) are effective for the ambulatory management of MPEs and are suggested by current guidelines 3–6. Catheters are generally well tolerated, and complications are uncommon and include infection, catheter dislodgement, and the development of loculation 4–8…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is proven to be a safe symptomatic procedure that improves the quality of life [66]. TPC is an alternative to pleurodesis for the treatment of recurrent MPE [74]. The advantages of the inserted TPC include clinically significant improvement in dyspnea, placement in the outpatient setting, and the ability of patient self-care at home.…”
Section: Management Of Mpementioning
confidence: 99%
“…[ 19 ] Another study found that peritoneum, pelvic effusion and jejunal wall thickness of patients were significantly decreased after using diuretic combined with external application of mirabilite. [ 6 ] Another study also indicated that the external application of mirabilite could effectively reduce peritoneum and weight of the patients with ascites, increase urine volume, and relieve abdominal distention in 8 to 10 days. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%